A Large Extra Cranial Cystic Trigeminal Schwannoma of the Parapharyngeal Space – Exploring the Right Approach - Krishnamurthy, Arvind (Indian J Surg Oncol, 2014)
Tumors of the parapharyngeal space (PPS) are uncommon, comprising less than 1 % of all head and neck neoplasm’s. Neurogenic lesions are the most common tumors of the poststyloid PPS accounting for nearly 25–30 % of all the PPS lesions. Schwannomas are uncommon nerve sheath tumors that may originate from any peripheral, cranial or autonomic nerve of the body, about one-third of them are known to arise in the head and neck region. Trigeminal schwannomas are known to arise from the root, ganglion, or intracranial portion of the three peripheral divisions of the nerve – ophthalmic (CN V1), maxillary (CN V2) and mandibular (CN V3). Schwannomas involving the mandibular division of the trigeminal nerve and localizing exclusively in the parapharyngeal space (PPS) is extremely rare and a surgical approach to such tumors has not been well established. The management of a PPS schwannoma is thus a clinical challenge, an adequate preoperative imaging with the identification of the possible nerve of origin allows for making informed decisions regarding the various approaches of management.